Students attitudes and behaviors in collaborative writing: A case in an Indonesian secondary school - Enur Nuraeni Rimayah; Abdul Rozak; Dede Endang Mascita (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2021)
This study is aimed at describing secondary school students attitudes and behaviors in collaboratively writing short story. Collaborative writing is used to identify indicators of collaborative activities. Designing a case study, one class of private secondary school that joined writing class participated in this study. Classroom observation and interview were employed to gather the data. The findings suggest that collaborative writing is conducted in five ways: active participation, productive collaboration, flexible and compromised works, good writing management, and respectful works. This research has implication in classroom writing to be promoted in the secondary school in Indonesia